Effects of basic type of intermittent exotropia on myopic shift in children: a 12-month observational study - Li, Jing-Xin; Liu, Xiang-Xiang; Hao, Jie; Li, Hui-Xin; Zhang, Qiong-Yue; Zhao, Yi-Yang; Wang, Yu-Meng; Li, Lei; Fu, Jing (Frontiers in Pediatrics, 2025)
BackgroundTo investigate the effect of basic intermittent exotropia (IXT) on myopic shift in children during 12-month follow-up.Methods165 children aged 4–15 years were recruited prospectively in this study and divided into 3 groups: Group A, consisted of 64 patients with basic IXT without surgery; Group B, consisted of 51 patients 1-month after IXT-corrected surgery; and Group C, consisted of 50 patients without any form of strabismus. All patients underwent assessments of spherical equivalent (SE), axial length (AL), exodeviation, and binocular function relating to accommodation and convergence. Examinations were conducted at baseline and 12-month. SE and AL changes were compared among groups. Univariate and multivariate linear analyses were employed to investigate the association between myopic shift and IXT, as well as other clinical parameters.ResultsThree groups showed comparable ages, genders and SEs at baseline (all P > .05). During 12-month follow-up, the rate of myopic shift varied among groups. Significant differences in SE progression (P = .006) and AL elongation (P = .014) between Group A and Group C were observed. Although SE progression and AL elongation in Group B were less than Group A, no significant differences were found (P = .125; P = .038). In the multivariate analysis, increases in exodeviation angle were significantly associated with both SE progression (β = 0.010, P = .041) and AL elongation (β = −0.005, P = .026). Each one prism diopter increase in the exodeviation angle was correlated with a 0.01D SE progression and a 0.005 mm AL elongation.ConclusionsChildren with basic IXT exhibited faster myopia shift compared to those without strabismus. Although surgical correction of strabismus appeared to slow this process, the effect was not statistically significant. Furthermore, greater increase in exodeviation angle was associated with higher rate of SE progression and AL elongation. Trial registrationThe study was approved by the Ethics Committee of Beijing TongRen Hospital (approved number: TRECKY2020-142, approved date: 2020.10.30).